Zwitterionic Design Principle of Nickel(II) Catalysts for Carbonylative Polymerization of Cyclic Ethers. Issue 43 (2nd October 2018) - Dai, Yiwei; He, Shiyu; Peng, Bangan; Crandall, Laura A.; Schrage, Briana R.; Ziegler, Christopher J.; Jia, Li
Abstract: Zwitterionic structure is necessary for Ni II complexes to catalyze carbonylative polymerization (COP) of cyclic ethers. The cationic charge at the Ni II center imparts sufficient electrophilicity to the Ni–acyl bond for it to react with cyclic ethers to give an acyl‐cyclic ether oxonium intermediate, while the ligand‐centered anionic charge ensures that the resultant oxonium cation is ion‐paired with the Ni 0 nucleophile. The current catalysts give non‐alternating copolymers of carbon monoxide and cyclic ethers and are the most effective when both ethylene oxide and tetrahydrofuran are present as the cyclic ether monomers. Abstract : Carbonylative polymerization : A zwitterionic nickel catalyst has been prepared for the copolymerization of cyclic ethers (ethylene oxide and tetrahydrofuran) with CO. The necessity for the Ni 0 nucleophile and the cyclic ether oxonium to exist as an ion pair requires the initial Ni II catalyst to be a zwitterion.